Let's solve the equation step by step.
Starting with the equation:
\[ -3x - 9 = -21 \]
First, add 9 to both sides of the equation:
\[ -3x - 9 + 9 = -21 + 9 \]
This simplifies to:
\[ -3x = -12 \]
Now, we divide both sides of the equation by -3:
\[ x = \frac{-12}{-3} \]
This simplifies to:
\[ x = 4 \]
So, to fill in the blanks:
-
After adding 9 to both sides, we have: \(-3x = -12\)
-
After dividing both sides by -3, we have: \(x = 4\)
Therefore, the completed solution looks like this:
- \(-3x = -12\)
- \(x = 4\)